PP2A Phosphatases Take a Giant Leap in the Post-Genomics Era - Bheri, Malathi; Pandey, Girdhar K. (Current Genomics, 2019)
Background: Protein phosphorylation is an important reversible post-translational modification, which regulates a number of critical cellular processes. Phosphatases and kinases work in a concerted manner to act as a “molecular switch” that turns-on or - off the regulatory processes driving the growth and development under normal circumstances, as well as responses to multiple stresses in plant system. The era of functional genomics has ushered huge amounts of information to the framework of plant systems. The comprehension of who’s who in the signaling pathways is becoming clearer and the investigations challenging the conventional functions of signaling components are on a rise. Protein phosphatases have emerged as key regulators in the signaling cascades. PP2A phosphatases due to their diverse holoenzyme compositions are difficult to comprehend. Conclusion: In this review, we highlight the functional versatility of PP2A members, deciphered through the advances in the post-genomic era.
Keywords: Ser/Thr phosphatases